Association of serum levels of secreted frizzled-related protein 5 and Wnt member 5a with glomerular filtration rate in patients with type 2 diabetes mellitus and chronic renal disease: a cross-sectional study - Báez, Indira Rojo; Castro, Daniel Omar Rivera; Gutiérrez, Sarahí Salas; López, Edgar Dehesa; Lemarroy, Adriana Aguilar; Suarez, Luis Felipe Jave; Ureta, Hipólito Castillo; Montoya, Edith Hilario Torres; Andalón, Vicente Olimón (São Paulo Medical Journal, 2020)
BACKGROUND: Diabetic nephropathy is a common complication of chronic kidney disease (CKD). Inflammation in the kidneys is crucial for promoting development and progression of this complication. Wnt member 5a (Wnt5a) and secreted frizzled-related protein 5 (Sfrp5) are proinflammatory proteins associated with insulin resistance and chronic low-grade adipose tissue inflammation. OBJECTIVE: To determine the correlation between serum Sfrp5 and Wnt5a concentrations and glomerular filtration rate in patients with type 2 diabetes mellitus and CKD. DESIGN AND SETTING: Cross-sectional, comparative and observational study in the Department of Endocrinology, Civil Hospital, Culiacán, Sinaloa, Mexico. METHODS: Eighty individuals with chronic kidney disease were recruited. Their serum Sfrp5 and Wnt5a concentrations were quantified using the enzyme-linked immunosorbent assay (ELISA) test. The statistical analysis consisted of the Mann-Whitney U test for independent samples and Spearman correlation, with statistical significance of P < 0.05. RESULTS: Serum Sfrp5 concentration continually increased through the stages of CKD progression, whereas serum Wnt5a concentration presented its highest levels in stage 3 CKD. Negative correlations be- tween estimated glomerular filtration rate (eGFR) and serum concentrations of Sfrp5 (r = -0434, P = 0.001) and Wnt5a (r = -0481, P = 0.001) were found. CONCLUSIONS: There were negative correlations between serum Sfrp5 and Wnt5a concentrations and eGFR at each stage of CKD, with higher levels in female patients. This phenomenon suggests that Sfrp5 and Wnt5a might be involved in development and evolution towards end-stage renal disease.